The effect of breathing technique on sticking region during maximal bench press - Dusan Blazek; Dominik Kolinger; Jan Petruzela; Petr Kubovy; Artur Golas; Miroslav Petr; Anna Pisz; Petr Stastny (Termedia Publishing House, 2020)
The intrathoracic pressure and breathing strategy on bench press (BP) performance is highly discussed in strength competition practice. Therefore, the purpose of this study was to analyze whether different breathing techniques can influence the time and track characteristics of the sticking region (SR) during the 1RM BP exercise. 24 healthy, male adults (age 23 ± 2.4 yrs., body mass 85 ± 9.2 kg, height 181 ± 5.4 cm) performed a 1 repetition BP using the breathing technique of Valsalva maneuver (VM), hold breath, lung packing (PAC), and reverse breathing (REVB), while maximum lifted load and concentric phase kinematics were recorded. The results of ANOVA showed that the REVB breathing decreased absolute (p < 0.04) and relative lifted load (p < 0.01). The VM showed lower (p = 0.01) concentric time of the lift than the other breathing techniques. The VM and PAC showed lower SR time than other breathing techniques, where PAC showed a lower SR time than VM (p = 0.02). The PAC techniques resulted in shorter SR and pre-SR track than other breathing techniques and the REVB showed longer SR track than the other considered breathing techniques (p = 0.04). Thus, PAC or VM should be used for 1RM BP lifting according to preferences, experiences and lifting comfort of an athlete. The hold breath technique does not seem to excessively decrease the lifting load, but this method will increase the lifting time and the time spend in the sticking region, therefore its use does not provide any lifting benefit. The authors suggest that the REVB should not be used during 1 RM lifts.